Kontekstualisasi Konsep Ulul Albab dalam Al-Qur'an sebagai Tujuan Pendidikan Islam di Era Transformasi Digital - Fathurohman, Salman (Al Mudzakarah, 2025)
Digital transformation presents new challenges for Islamic education, particularly in maintaining holistic and Qur’anic-oriented educational goals amid rapid technological advancement. Islamic education is required not only to produce learners who are technologically competent but also spiritually grounded, intellectually reflective, and morally responsible. One of the fundamental Qur’anic concepts relevant to this objective is Ulul Albab. This study aims to conceptualize Ulul Albab holistically as a goal of Islamic education in the era of digital transformation, analyze its relevance and implications for curriculum design and learning strategies, and formulate an Ulul Albab-based conceptual framework for contemporary Islamic education. This research employs a qualitative approach through a conceptual study and thematic analysis of Qur’anic verses related to Ulul Albab, particularly Q.S. Āli ‘Imrān [3]: 190–191 and Q.S. Az-Zumar [39]: 9, supported by classical and contemporary Qur’anic exegesis. The findings indicate that Ulul Albab encompasses spiritual, intellectual, moral, and social dimensions that remain highly relevant as a normative foundation for value-oriented and ethical Islamic education in the digital age.